2020
DOI: 10.1038/s41598-020-64783-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal optical imaging technique to visualize progressive axonal damage after brain injury in mice reveals responses to different minocycline treatments

Abstract: A high-resolution, three-dimensional, optical imaging technique for the murine brain was developed to identify the effects of different therapeutic windows for preclinical brain research. This technique tracks the same cells over several weeks. We conducted a pilot study of a promising drug to treat diffuse axonal injury (DAI) caused by traumatic brain injury, using two different therapeutic windows, as a means to demonstrate the utility of this novel longitudinal imaging technique. DAI causes immediate, spora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Previous preclinical studies have reported efficacy of minocycline for brain injury with dosing ranging from 22.5 to 90 mg/kg/dose [ 19 , 24 , 32 , 49 ]. We designed a two-step funnel design for four different dosing regimens of minocycline with an initial evaluation of efficacy using short-term neuropathology followed by selecting the most efficacious dosing for long-term behavioral outcome studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous preclinical studies have reported efficacy of minocycline for brain injury with dosing ranging from 22.5 to 90 mg/kg/dose [ 19 , 24 , 32 , 49 ]. We designed a two-step funnel design for four different dosing regimens of minocycline with an initial evaluation of efficacy using short-term neuropathology followed by selecting the most efficacious dosing for long-term behavioral outcome studies.…”
Section: Methodsmentioning
confidence: 99%
“…Minocycline is a broad-spectrum tetracycline antibiotic, which has been studied as a neuroprotective agent in TBI [ 32 , 43 , 46 ]. Although minocycline is proposed to have pleiotropic effects on the brain, the main mechanism of action for neuroprotection is thought to be suppression of microglial activation after TBI [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…By combining the FPI model and in vivo imaging using highresolution gradient index lens technology, the Murray group was able to examine axonal changes in the same mouse and visualized axonal morphology from external capsule in both preinjury and post-injury stages for up to 60 days after injury. They found axonal varicosities and undulated axons 1 h post injury (Pernici et al, 2019(Pernici et al, , 2020. Administration of minocycline to reduce microglia activation for three days starting 1 or 72 h after injury inhibited axonal varicosity formation or promoted axon recovery, respectively (Pernici et al, 2020).…”
Section: Axonal Varicosities Induced By Mechanical Impact In Vivomentioning
confidence: 99%
“…They found axonal varicosities and undulated axons 1 h post injury (Pernici et al, 2019(Pernici et al, , 2020. Administration of minocycline to reduce microglia activation for three days starting 1 or 72 h after injury inhibited axonal varicosity formation or promoted axon recovery, respectively (Pernici et al, 2020). Despite clear advantages, the in vivo imaging often involves extensive experimental procedure in order to examine a limited number of axons in a highly focused brain regions.…”
Section: Axonal Varicosities Induced By Mechanical Impact In Vivomentioning
confidence: 99%
“…At an early stage of damage, axons have the potential to recover but once mechanical or molecular processes fragment the axon, then irreversible axon degeneration proceeds [ 35 , 48 , 51 , 52 , 57 , 79 , 80 ]. Use of transgenic mice with fluorescent labeling of axons has shown that axonal swellings can appear within minutes of an insult and recover within hours, or persist for weeks or more, and can degenerate to form terminal end bulbs at sites of disconnection [ 35 , 57 , 59 , 78 ]. Axons can also continue to initiate distal, or Wallerian, degeneration in the days to weeks after an initial mechanical injury [ 52 ].…”
Section: Introductionmentioning
confidence: 99%